STUDY ON MECHANICAL PROPERTIES OF SPATIAL INTERSECTION CONCAVE HONEYCOMB STRUCTURE (Jixie qiangdu)
As a typical negative Poisson's ratio structure,the concave hexagon is commonly used in modern energy absorption devices.Based on the honeycomb structure and the concave hexagon,five kinds of structures were firstly obtained through space intersection design.The deformation mechanism and structural mechanical characteristics of five kinds of structures were discussed by finite element simulation and compression test.Then,the transient equivalent calculation method of structural counter-force was given by using vector analysis method,and the calculation formulas of counter-force,collision velocity and acceleration were derived.Counter-force calculation results were compared with compression test,and the test results were basically consistent with the theoretical results.Finally,the optimal structure was filled into the crash box,and the collision simulation analysis was processed with the new crash box.It is found that the mechanical properties of concave honeycomb stucture(CHS)cells with negative Poisson's ratio are better than those of the traditional honeycomb structure(THS).In the second type of structure,C-C structure can increase the structural deformation and reduce the stress.And the stress distribution of C-C structure is more uniform than that of the other structure.The collision simulation results show that the C-C structure crash box can greatly reduce the peak values of speed and acceleration,and the acceleration value is far less than the 40g,which reaches standard in the vehicle collision specification.At the same time,compared with the traditional crash box structure,the energy absorption of the new designed sandwich structure crash box is improved by more than 3 times.